Low-Cost Instrumentation for Measuring Soil Respiration in Nature-Based Carbon Mitigation Studies - Harry John, Kuling; Lidyana, Roslan; Shanti Faridah, Salleh (IEEE XPLORE, 2025)
Accurate measurement of soil CO₂ flux is essential for understanding terrestrial carbon dynamics and evaluating the effectiveness of nature-based solutions (NbS) for climate change mitigation. This study introduces a costeffective, field-deployable system developed at Universiti Malaysia Sarawak (UNIMAS) to monitor soil respiration across various land-use types. The system integrates readily available sensors to measure CO₂ concentration (MG811), air pressure and temperature (BMP180), and soil moisture (YL69), all coordinated via an Arduino microcontroller for realtime data logging and control. The setup utilizes a static closedchamber design, carefully engineered to quantify CO₂ efflux while minimizing environmental disturbances and maintaining system portability. Designed with affordability and adaptability in mind, the instrument was tested across three ecologically distinct environments: secondary forests, natural wetlands, and managed grasslands. Data collected over timed intervals enabled calculation of CO₂ fluxes using changes in concentration and environmental parameters. The results demonstrated clear variations in flux across ecosystems, with higher variability observed in grasslands, moderate emissions in forest soils, and fluctuating patterns in wetlands due to anaerobic conditions. Sensor performance was stable and responsive under field conditions, particularly within the optimal temperature range for the MG811 sensor (20–50°C). The supporting environmental sensors (BMP180 and YL-69) enhanced contextual interpretation of respiration patterns. The system’s low cost and ease of deployment position it as a promising tool for expanding soil carbon monitoring, particularly in resource-limited settings. Its potential integration into broader NbS frameworks underscores the value of intelligent, accessible instrumentation in advancing ecosystem-based climate solutions.